Hydro-structural stability investigation of a 100 MW Francis turbine based on experimental tests and numerical simulations. (December 2019) - Decaix, J; Hasmatuchi, V; Titzschkau, M; Rapillard, L; Münch-Alligné, C
Abstract: This work focuses on a 100 MW Francis turbine prototype, part of one of the four horizontal ternary groups of Grimsel 2 PSPP, in Switzerland. Due to the massive integration of new renewable energy, the number of daily starts/stops of the machines has increased. Consequently, cracks on the runner blades of the Francis turbines have been noticed, without a clear explanation regarding the phenomenon responsible for their onset. To identify the main stress-full operating condition causing these cracks, the full turbine hill chart has been covered during the in situ measurement campaign including start-up, speed no-load, deep part load, best efficiency, full load and shut-down operating conditions. Then hydro-structural stability diagnosis diagrams of the prototype have been established for the whole operating range of the turbine. In addition, CFD numerical simulations for different operating conditions, along with FEM structural and modal analysis of the runner, have been carried out. The onboard measurements evidenced the highest mechanical stresses on the runner blades at speed no-load operating condition. This conclusion is supported by CFD and FEM analysis, which put in evidence the possible excitation of one of the runner's eigen frequency by the fluctuations of the pressure field.